Production regime and associated N cycling in the vicinity of Kerguelen Island, Southern Ocean (2015)
ABSTRACT: Although the Southern Ocean is considered a high-nutrient, low-chlorophyll (HNLC) area, massive and recurrent blooms are observed over and downstream of the Kerguelen Plateau. This mosaic of blooms is triggered by a higher iron supply resulting from the interaction between the Antarctic Circumpolar Current and the local bathymetry. Net primary production, N uptake (NO−3 and NH+4), and nitrification rates were measured at eight stations in austral spring 2011 (October–November) during the KEOPS 2 cruise in the Kerguelen Plateau area. Natural iron fertilization stimulated primary production, with mixed layer integrated net primary production and growth rates much higher in the fertilized areas (up to 315 mmol C m−2 d−1 and up to 0.31 d−1 respectively) compared to the HNLC reference site (12 mmol C m−2 d−1 and 0.06 d−1 respectively). Primary production was mainly sustained by nitrate uptake, with f ratios (corresponding to NO−3-uptake / (NO−3-uptake + NH+4-uptake)) lying at the upper end of the observations for the Southern Ocean (up to 0.9). We report high rates of nitrification (up to ∼ 3 μmol N L−1 d −1, with ∼ 90 % of them < 1 μmol N L−1 d−1) typically occurring below the euphotic zone, as classically observed in the global ocean. The specificity of the studied area is that at most of the stations, the euphotic layer was shallower than the mixed layer, implying that nitrifiers can efficiently compete with phytoplankton for the ammonium produced by remineralization at low-light intensities. Nitrate produced by nitrification in the mixed layer below the euphotic zone is easily supplied to the euphotic zone waters above, and nitrification sustained 70 ± 30 % of the nitrate uptake in the productive area above the Kerguelen Plateau. This complicates estimations of new production as potentially exportable production. We conclude that high productivity in deep mixing system stimulates the N cycle by increasing both assimilation and regeneration.